The sport training process of para-athletes: A systematic review - Macías, M. R.; Fuentes-Guerra, F. J. G.; Robles, M. T. A. (International Journal of Environmental Research and Public Health, 2022)
The aim of this systematic review was to identify the main factors affecting the training process of para-athletes, as well as the barriers they encounter. For this purpose, a systematic review was carried out in accordance with the PRISMA declaration guidelines, in which six databases were analysed (Web of Science, Scopus, SportDiscus, Pubmed, Eric, and PsycInfo). A total of 19 articles were selected for analysis after applying the inclusion criteria. The results show that the figures of the coach and families in the sporting and social contexts, respectively, had a relevant influence on the training process of para-athletes. Furthermore, in terms of psychological aspects, stress reduction, the importance of self-esteem, and motivation were highlighted. On the other hand, there are some barriers hindering the training and performance of athletes, which are related to the lack of financial support, lack of visibility in the media, and dependence on other people. These considerations can be of great help to coaches and competent institutions in the field (Paralympic committees, federations, etc.) in order to improve the training process and performance of para-athletes and to eliminate the barriers encountered by this group, promoting policies which facilitate access to sports for people with disabilities.